Evaluasi Sistem Pemilu dan Ambang Batas Parlemen di Indonesia - M Zidny Ilman Nafian (Fakultas Hukum Universitas Islam Indonesia, 2024)
The proportional electoral system has given rise to differences in the perspective of popular sovereignty. With careful consideration regarding the establishment of a proportional electoral system, it is hoped that elections can be created based on people's sovereignty. It is considered that the determination of parliamentary thresholds still needs to be reviewed. Determining the electoral system and parliamentary thresholds is a fundamental problem in organizing elections in Indonesia. This research uses normative research methods with a normative juridical approach, which is based on statutory regulations, opinions of legal experts, and factual case studies. Data collection techniques were carried out through literature studies from books, journals, articles and statutory regulations. The data analysis technique used in this research is a qualitative data analysis technique which refers to the facts and data that have been collected. Based on the results of the research, the author found several shortcomings in determining the 4% parliamentary threshold which requires further study in determining it. The author believes that a closed proportional system with the proposed adjustments can be the right solution to advance democracy in Indonesia, while maintaining political stability and fair representation for all Indonesian people.